PTGS2-899G>C and prostate cancer risk: a population-based nested case-control study (ProtecT) and a systematic review with meta-analysis. - Murad, A; Lewis, S; Smith, G; Collin, S; Chen, L; Hamdy, F; Neal, D; Donovan, J; Martin, R (2009)
Prostaglandin endoperoxidase synthase 2 is a key regulator of inflammation and may play a role in prostate carcinogenesis. The polymorphism, -899G>C (rs20417), alters a transcription factor-binding site and is associated with a reduced risk of colorectal adenoma. We tested the hypothesis that rs20417 may influence prostate cancer risk, using a large case-control study (n(cases)=1608, n(controls)=3058). We found no evidence that rs20417 alters prostate cancer risk (odds ratio (OR(CC and GC v GG)=1.05, 95% confidence interval (CI)=0.91-1.20). A meta-analysis of three studies also found little evidence that rs20417 alters risk (pooled OR(CC and GC v GG)=1.04, 95% CI=0.93-1.17), making it unlikely that rs20417 contributes in any major way to prostate cancer aetiology.